Eksistensi Guru Sebagai prIbadi Yang Profesional Dan Inspiratif - Inan Tihul (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2020)
The teacher in public perspectively is the individual who applicates education in certainty places, is does not have to in educationally formally, but can be in mosques, small mosques, houses, etc. Teacher is assignment an tasked tittle in professional sector, to concern something involved whole of educational prossesing. The profesinal teacher will be reflected in doing sacrifices tasks that is sined with good skills in matters or methodes. Besides that also is shown by his or her responsibillity to do all sacrifices assignments. The profesional teacher should be able to bring and fulltil it’s responsibilities for educaters, parents, public, nation, state, and religiousmen. The professional teacher is has a responsible personality, social, aspects, intellectual, morallity values, spiritual approach. The independent responsible personality who able to understanding about him or her self and develoving of become inspirated for every human